(untitled) (Journal of Applied Oral Health and Dental Therapy (JAOHDT), 2026)
Gingivitis is a common periodontal disease that can affect various aspects of oral health, including the fulfillment of basic human needs according to the concept of Darby and Walsh. This study aimed to determine the profile of basic human needs according to Darby and Walsh among clients of working age (15–64 years) with gingivitis at the Periodontology Clinic of the Hasanuddin University General Hospital. The study employed a descriptive design with a cross-sectional approach conducted from January to February 2026. The sampling technique used total sampling with a sample size of 77 respondents. Data collection was performed through clinical examinations based on the concept of oral health care, followed by descriptive analysis using frequency distributions and percentages. The results showed that the majority of respondents were in the 15–24 age group (61.04%) and were female (63.64%). Of the total 108 identified basic human needs, the most unmet need was responsibility for oral health, with 71 cases (65.74%), followed by good biological condition and dental function with 19 cases (17.59%), and a healthy facial appearance with 18 cases (16.67%). This study indicates that the primary issues among gingivitis patients are not only related to the biological condition of periodontal tissues but also to behavioral aspects of oral health maintenance. Therefore, promotive and preventive efforts are needed to enhance individual responsibility for oral health.